Analysis of Partnership Program Implementation by PT. Jasa Marga (PERSERO) Tbk Belmera Branch Against UMKM Empowerment - Nadia Amalia; Marliyah Marliyah (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2022)
The researcher identified clear theoretical gaps in previous research related to environmental development. The theory about it is that in the implementation of the partnership program in MSME Empowerment, it is explained that business partners are said to be successful with the help of this program, if the monthly loan installment payments are said to be smooth but the investigation in practice is different from the provisions that should be enforced by PT Jasa Marga. used in data collection is a qualitative approach with descriptive research methods. This study uses two types of data sources, namely Primary Data and Secondary Data according to the grouping of information or data that has been obtained. Partnership Program run by PT. Jasa Marga (Persero) Tbk Belmera Branch is very influential for the welfare of MSME actors who need loan funding assistance to expand their business or business and this is based on the terms and criteria that apply to make loans. So that the Partnership Program implemented by PT. Jasa Marga's Belmera Branch is running smoothly and continuously increasing, it is required to select prospective foster partners properly and correctly so that there is no congestion in payments.